Government debt forecast errors and the net expenditure rule in EU countries - David Cronin; Kieran McQuinn (The Economic and Social Research Institute (ESRI), 2023)
Against a backdrop of debt ratio targets being central to recent proposed changes to the EU fiscal rules, we examine errors in official forecasts of the General Government debt ratios and their determinants in 26 member states from 2012 to 2019 when the "six pack" rules applied. We find debt ratio outturns exceeding projected values with forecast errors increasing over a four-year horizon. Larger errors arise where the initial debt ratio exceeds the Maastricht Treaty threshold of 60 per cent. In modelling the forecast errors of the debt ratio, we find that most of the variation is explained by forecast errors in the output growth rate and in the structural budget balance, as well as previous errors in projecting the debt ratio. During the sample period, member states who had not met their medium-term objective of a balanced structural budget were expected to adhere to a net expenditure rule. For countries subject to this requirement, we find undue optimism arising in forecasting the deficit ratio, a determinant of the debt ratio.
Keywords: H30; H63; H68; 330; EU fiscal rules; government debt; forecast errors